Implementasi Program Komunitas Belajar Dalam Meningkatkan Kompetensi Guru : Penelitian - Arta Mulya Budi Harsono; Sofie Dhiya Maharani Dhiya; Ahmad Suriansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research is motivated by the gap between the demands of the independent curriculum and teachers' readiness to implement it, particularly in terms of pedagogical competence. The purpose of this study is to analyze the implementation, impact, obstacles, and solutions of the teacher learning community program in improving teacher competence. This research used a qualitative approach with a case study design at SDN Kelayan Selatan 2 Banjarmasin. Data were collected through structured interviews with the principal, nonparticipant observation, and documentary analysis. The results indicate that the teacher learning community is an effective collaborative platform for teachers to share experiences, improve pedagogical competence, and innovate in project-based learning. This program also has a positive impact on increasing self confidence, collaboration, and communication between teachers and the principal. However, obstacles such as limited resources, time, and motivation remain a barrier to implementation. The principal plays a crucial role through reflective supervision, the use of digital media, and providing appreciation to maintain teacher motivation. Overall, the learning community program has proven effective as a model for teacher professional development that supports the successful and sustainable implementation of the independent curriculum.